Estimation of Fe2O3 in Haematite Ore of Hospet by Iodo-Potentiometric Technique - Suma, N.; Jeevan, T.; Palanna, O.G. (Asian Journal of Chemistry, 2010)
A successful attempt is made to estimate ferric oxide (Fe2O3) in haematite, an iron ore obtained from Hospet mining area (Karnataka) by iodo-potentiometric method. Both iodometric and potentiometric investigations are carried out in a single two-in-one cell to obtain the data related for the estimation of Fe2O3 in haematite ore. A quantitative relationship is observed between the potentials, EM and the volumes of standard sodium thiosulphate consumed (at the end point) in potentiometric and volumetric titrations. These potentials, EM, are again found to have a linear relationship with the weight of the ore sample taken. The titre volumes (v1 and v2 mL) of both potentiometric and iodometric methods are identical. Interestingly, the estimation of Fe2O3 in haematite ore is possible in the light of the above relationships observed. An excellent conformity of results are observed for potentiometric, iodometric and volumetric (Sn reduction method) titration data for the estimation of the percentage of Fe2O3 in haematite ore.